COMMUNITY GUIDANCE ASSIGNMENT PANDEMIC OVID-19 AND NEW NORMAL PREPARATION IN CLASS I CORRECTIONAL HALL OF BANDUNG - Vivi Sylviani Biafri (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
The spread of corona virus in Indonesia is known to occur in March 2020 with positive corona cases found in Depok, West Java. Within 3 months, most cities in Indonesia contained corona patients. In July 2020, the Indonesian people will start a new life. This new life order will be applied to all walks of life. Changes will occur for civil servants or private employees in carrying out daily tasks. One of the experienced changes is Community Guidance. Community Guidance is a civil servant within the Directorate General of Corrections of the Ministry of Justice and Human Rights. These Community Guides have direct contact with their clients. Therefore, we need innovations to do the work. The research question is How does the Community Guidance do their work during the co-19 pandemic and new normal preparations at Class I Correctional Hall of Bandung? What impact will it have on Community Guidance at Class I Correctional Hall of  Bandung? The purpose of this research is to analyze how the Community Guidance in carrying out tasks in the co-19 pandemic and the preparation of new normal and their impact on them. This study uses a qualitative method. The approach used is a descriptive approach. The research location is Class I Correctional Hall of Bandung. The results showed that the community guidance in carrying out their tasks during the co-19 pandemic used a lot of information technology. Therefore, community guidances are required to be able to operate the applications used